Trade relations with the Communist countries - Bernd Kunze (Intereconomics, 1973)
After the Federal Republic of Germany, Japan is the second largest trade partner of the Communist countries as a whole and of the Soviet Union and the largest partner of the People's Republic of China. It has only been in recent years that Japan gained this formidable position in the trade with the East.
Keywords: 330; Japan